1996
DOI: 10.1128/mcb.16.8.4248
|View full text |Cite
|
Sign up to set email alerts
|

The A1 · U72 Base Pair Conserved in Eukaryotic Initiator tRNAs Is Important Specifically for Binding to the Eukaryotic Translation Initiation Factor eIF2

Abstract: The formation of a specific ternary complex between eukaryotic initiation factor 2 (eIF2), the initiator methionyl-tRNA (Met-tRNA), and GTP is a critical step in translation initiation in the cytoplasmic proteinsynthesizing system of eukaryotes. We show that the A1 ⅐ U72 base pair conserved at the end of the acceptor stem in eukaryotic and archaebacterial initiator methionine tRNAs plays an important role in this interaction. We changed the A1 ⅐ U72 base pair of the human initiator tRNA to G1 ⅐ C72 and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…The A1:U72 base pair influences multiple steps of initiation Multiple studies, both in vivo andinvitro, have shown that the A1:U72 base pair in the acceptor stem of the initiator tRNAisacritical binding determinant for eIF2 (von PawelRammingen et al 1992;Astrom et al 1993;Farruggio et al 1996;D rabkin and RajBhandary 1998; Kapp and Lorsch 2004a). The results of our study indicate that, in addition to its key role in eIF2 d GTP d Met-tRNA i ternary complex formation, the A1:U72 base pair influences later steps in the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The A1:U72 base pair influences multiple steps of initiation Multiple studies, both in vivo andinvitro, have shown that the A1:U72 base pair in the acceptor stem of the initiator tRNAisacritical binding determinant for eIF2 (von PawelRammingen et al 1992;Astrom et al 1993;Farruggio et al 1996;D rabkin and RajBhandary 1998; Kapp and Lorsch 2004a). The results of our study indicate that, in addition to its key role in eIF2 d GTP d Met-tRNA i ternary complex formation, the A1:U72 base pair influences later steps in the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the A1:U72 base pair in tRNA i Met by G1: C72, as found in tRNA e Met , impaired yeast cell growth (von Pawel-Rammingen et al 1992;Astrom et al 1993), binding of Met-tRNA i Met to eIF2 (Farruggio et al 1996;Kapp et al 2006), and TC binding to the 40S ribosome (Kapp et al 2006). Thus the identity of this base pair contributes both to TC formation and to later steps in the initiation pathway.…”
Section: Initiator Methionyl-trnamentioning
confidence: 99%
“…Total tRNA from yeast was isolated as described (26). The extent of aminoacylation was determined by fractionation of the tRNAs by acid-urea gel electrophoresis, followed by detection of the suppressor tRNAs by Northern blot hybridization with specific oligonucleotide probes (27).…”
Section: Extent Of Aminoacylation Of Suppressor Trnas In Vivomentioning
confidence: 99%